Experimentação Agroecológica: Descrição de práticas visando a sustentabilidade rural e ambiental - Pereira, Adriana Mendes (2017)
Agribusiness has projected onto the planet a new model of field development. In industrial agriculture, the process of simplifying the environment has promoted changes in natural ecosystems to optimize and expand food production in order to meet growing population demand. This stimulation of the sector happened through genetic improvement, mechanization of large areas, development of agrochemicals and application of precision agriculture. However, this conventional model put at risk the sustainability of agricultural activity. Throughout this dissertation, we will try to verify the main practices employed in the agroecological transition process, to understand the motivations related to sustainable food production. To this end, we carry out literary reviews about the advantages of agroecological production and the challenges faced by family agriculture inside and outside social movements; we investigated through experiences, observations, interviews and practices the construction of the agroecological knowledge of formerly conventional farmers; and systematize the reconstruction of the land by campesinos of the social movement of agrarian reform aiming at the sustainable development of rural and environmental activities. With this purpose, we analyze the data obtained for the construction and systematization of experiences, we evaluate the actions of organizing, recording and assimilating the experiences to promote the understanding of the facts, relationships and peculiar issues of each space. For this, the shared experience generated knowledge and information relevant to the construction of ecological knowledge, the deficiencies faced by family agriculture, mainly related to restricted technical assistance, low governmental incentive and the prejudices attributed to the practices involved in the production of sustainable food. The entire process of knowledge construction has revealed the challenges to be overcome from the correct management of the soil to the dissemination of ecological knowledge.